Neutralising and Non-neutralising Antibodies to SARS-CoV-2: Role during Infection and in the Evolution of Antigenic structure - S. K. Pylaeva; A. A. Sinyugina; L. I. Kozlovskaya; E. A. Artamonova; A. A. Erovichenkov; R. F. Sayfullin; I. V. Gordeychuk; A. A Ishmukhametov (Эпидемиология и вакцинопрофилактика, 2025)
Relevance. COVID-19, caused by the SARS-CoV-2 virus, remains a global public health threat despite the end of the pandemic. In the four years since the onset of the pandemic, the SARS-CoV-2 genome has undergone significant changes, particularly in the gene encoding the spike (S) protein. These changes resulted from the accumulation of immune responses in the human population, allowing the virus to evade the immune response. A significant proportion of the population was infected early in the pandemic or vaccinated with vaccines based on earlier variants of the virus. The emergence of new mutant variants raises concerns about the potential for severe COVID-19 in previously infected or vaccinated individuals.Аim. To examine the specifics of antibody formation, as well as the spectrum and functional activity of these antibodies in patients with COVID-19.Conclusions. Antibodies produced in response to infection or vaccination show diversity in spectrum and functional activity. Changes in the viral genome may reduce antibody effectiveness, highlighting the importance of monitoring new SARS-CoV-2 variants and developing adapted vaccines. These data will be key in shaping COVID-19 vaccination and treatment strategies in a changing epidemiological situation.